The Trickster: A Political Theology for Our Time - Eller, Jack David (Socio-historical examination of religion and ministry, 2023)
Political theology has traditionally been dominated by Christian concepts, specifically the concept of a law-giving and order-preserving god. Other political theologies are possible, however, and this essay considers one—the trickster—a culture hero and comic buffoon who delightedly and shamelessly violates and subverts order to inaugurate a new reality of his own making, if not of his own will. The first half of the essay introduces the trickster as a cross-cultural agent of creative destruction, a messenger and civilization-bringer, and a clever fool. The second half explores how the last two centuries of Western social and intellectual history have shifted the ground from under a god of order toward a spirit of flux, transience, paradox, and liminality. The essay concludes that the contemporary post-modern state of permanent liminality is better symbolized and grasped through the mythical lens of the trickster than the biblical god, including and especially contemporary global right-wing populism, whose leading figures reflect the wicked energy and appeal of the trickster impulse.